Development of paper-based biosensor for point-of-care- nucleic acid testing / Choi Jane Ru - Choi, Jane Ru (2016)
Nucleic acid testing (NAT), a molecular diagnostic technique that involves nucleic acid extraction, amplification and detection, conventionally relies on well-established laboratories, high-end instrumentation and highly trained operators, limiting its use in resource-poor settings, where most diseases exist. With advances in point-of-care testing (POCT), lateral flow assays (LFA) have been explored for nucleic acid detection. However, as biological samples are generally complex and contain low amounts of target nucleic acids, a substantial off-chip extraction and amplification process (e.g., tube-based extraction and polymerase chain reaction (PCR)) is normally required prior to lateral flow detection. Additionally, the applications of LFA have been currently limited by their low sensitivity and poor functionality. Herein, it was demonstrated for the first time a novel fully integrated paper-based sample-to-answer biosensor incorporating nucleic acid extraction, amplification and sensitive lateral flow detection. The optimum concentration of reagent and environmental conditions (i.e., temperature and relative humidity) for LFA were determined. Paper-based LAMP was integrated into LFA, coupled with a handheld battery-powered heating device for nucleic acid amplification in POC settings, which showed a comparable result to that of conventional tube-based platform. A fully integrated paper-based sample-to-answer biosensor was then developed, which could successfully detect Escherichia coli in spiked drinking water, milk, blood, and spinach with a detection limit of as low as 10- 1000 CFU/mL, and Hepatitis B virus (HBV) in clinical blood sample, highlighting its potential use in medical diagnostics, food safety analyses and environmental monitoring. The sensitivity of biosensor was further enhanced by incorporating a piece of paperbased shunt and a polydimethylsiloxane (PDMS) barrier into the strip to achieve optimum fluidic delays for LFA signal enhancement, resulting in 10-fold signal iv enhancement over unmodified LFA. This strategy could successfully detect HBV with concentrations of as low as ~102 IU/mL in clinical blood samples, which was comparable to that of conventional detection strategy and even more sensitive than the existing biosensors, demonstrating its ability to detect acute HBV infections. The phenomena of fluidic delay were also evaluated by mathematical simulation, through which the fluid movement throughout the shunt and the tortuosity effects in the presence of PDMS barrier were revealed, which significantly affect the detection sensitivity. The proposed fully integrated biosensor offers great potential for highly sensitive detection of various targets for wide applications in the near future.